1984
DOI: 10.1200/jco.1984.2.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemotherapy and radiation therapy for patients with cancer of the esophagus: a potentially curative approach.

Abstract: Twenty-one patients with squamous cell cancer of the esophagus were entered into a pilot clinical trial using preoperative chemotherapy (5-fluorouracil and cis-platinum) and radiation with the intent of improving cure rate and survival. After the preoperative treatment was complete, 15 patients (71%) were resected for cure. Seven (47%) of 15 had no histologic evidence of cancer in the resected esophagus, but two of these had microscopic cancer in resected lymph nodes. The median survival for all patients enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(71 citation statements)
references
References 3 publications
2
66
1
Order By: Relevance
“…The rst study reported from Wayne State University appeared promising, achieving a histologic complete response rate of 26% and a median survival of 18 months. Moreover, all complete responders were alive after two years (38). Similar results have been reported from other groups (39).…”
Section: Randomized Trialssupporting
confidence: 80%
“…The rst study reported from Wayne State University appeared promising, achieving a histologic complete response rate of 26% and a median survival of 18 months. Moreover, all complete responders were alive after two years (38). Similar results have been reported from other groups (39).…”
Section: Randomized Trialssupporting
confidence: 80%
“…The value of chemoradiotherapy for the treatment of unresectable oesophageal carcinoma remains controversial, and only a few clinical studies have been published since the 1980s (Leichman et al, 1984;Leichman et al, 1987;Poplin et al, 1987;Coia et al, 1991;Herskovic et al, 1992;Frorastiere et al, 1993;Poplin et al, 1994). Most patients in these studies had local -regional disease (UICC stage I or II).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported successful results with these modalities, either with or without surgery, against local -regional carcinoma (Leichman et al, 1984;Leichman et al, 1987;Poplin et al, 1987;Coia et al, 1991;Frorastiere et al, 1993;Poplin et al, 1994). The combination of 5-fluorouracil (5-FU) and cisplatin (CDDP) has become a standard regimen, not only because of the clinical outcome but also because of the synergism between the two agents and their radiosensitising effects (Douple et al, 1980;Scanlon et al, 1986;Byfield, 1990).…”
mentioning
confidence: 99%
“…Of the 71% of patients who underwent curative resection, pathologic complete responses in the primary tumor site were detected in 47%, and a 27% operative mortality rate was observed. The median survival time for good responders was 24 months, and median survival time was 18 months for all patients enrolled in the study [62]. The Southwest Oncology Group (SWOG) 8037 trial, which evaluated 113 patients, used a similar regimen of concurrent 5-FU and cisplatin and 30 Gy of radiation before surgery.…”
Section: Neoadjuvant Chemoradiotherapymentioning
confidence: 99%
“…Several nonrandomized trials from different institutions have reported good response rates from neoadjuvant chemoradiation [57][58][59][60][61][62][63][64][65][66][67][68][69][70]. Jones and colleagues from the University of North Carolina at Chapel Hill (Chapel Hill, NC) showed minimal toxicities from 45 Gy of radiation therapy combined with 5-FU and cisplatin chemotherapy given prior to surgery.…”
Section: Neoadjuvant Chemoradiotherapymentioning
confidence: 99%